Policy complexity and implementation performance in the European Union - Maximilian Haag; Steffen Hurka; Constantin Kaplaner (Regulation & Governance, 2024)
This study examines the relationship between the complexity of EU directives and their successful implementation at the national level. Moving beyond the state-of-the-art, we propose a comprehensive framework considering structural, linguistic, and relational dimensions of policy complexity. We argue that policy complexity entails higher transaction costs, hindering effective implementation. Using a novel dataset covering roughly 1000 directives from 1994 to 2022, we find strong evidence of policy complexity negatively impacting implementation performance. Moreover, we find that states with higher administrative capacity are better able to process high complexity efficiently and that Eurosceptic member states attract fewer infringement proceedings in highly complex policy environments than Europhile member states. This could alternatively point to strategic enforcement behavior of the Commission or to bureaucracies that are less Eurosceptic than their political masters might wish for. Our study thereby contributes to a deeper understanding of the challenges of successful implementation of EU directives.
Keywords: 330; capacity; Euroscepticism; European Union; implementation; performance; policy complexity